Uji Tingkat Efikasi Herbisida Berbahan Aktif Bispiribac Sodium Terhadap Gulma Daun Sempit Pada Tanaman Padi (Oryza Sativa L.) Varietas Ciherang: Uji Tingkat Efikasi Herbisida Berbahan Aktif Bispiribac Sodium Terhadap Gulma Daun Sempit Pada Tanaman Padi (Oryza Sativa L.) Varietas Ciherang - Muhammad Triesa Zakaria; Muhammad Syafi'i; Darso Sugiono (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
Rice is a food crop that is widely cultivated by farmers in Indonesia and is a staple food ingredient that must be available and fulfilled. Weeds are strong natural competitors for rice plants because they are able to produce seeds in large quantities which make germination fast at the beginning and a long life cycle with a very high density. evenly in each region. The research was carried out at the Experimental Garden in Adiarsa Timur Village, East Karawang District, Karawang Regency, West Java. The research location is 15 m above sea level (masl), the average temperature is at least 300C and a maximum of 340C. And the classification according to the Schmidt and Ferguson rainfall classification is in the D medium rainfall type. The time of this research starts from January 2020 to April 2020. The design method that will be used in this study is an experimental research method using a Randomized Block Design. The treatments in the study were 7 treatments with 4 (four) replications. With treatment A = Bisspiribac Sodium 105 ml/ha, B = Bisspiribac Sodium 157.5 ml/ha, C = Bisspiribac Sodium 210 ml/ha, D = Bisspiribac Sodium 262.5 ml/ha, E = Bispiribac Sodium 315 ml/ha , F = Hand weeding and G = Control Without Control. The results showed that based on the results of the study, the herbicide treatment with the active ingredient Bispiribac sodium controlling narrow leaf weeds in rice fields (Oryza sativa .L) had a significant effect on the growth power of weeds at the beginning of growth. Treatment at code E with a dose of 0.62 ml/plot, provided effective weed control.